Can children's religiosity be built through family's religious culture and the discipline in attending TPA at school? - Tampi Prehadini; Anwar Senen; Ali Mustadi (Jurnal Prima Edukasia, 2021)
This study aims to find out the effects of family’s religious culture and the discipline in attending ‘Taman Pendidikan Al Qur’an (TPA) at school on the first grade students’ religiosity. This study used the ex-post facto quantitative approach, while the population was all first grade student in Pengasih District, Kulon Progo regency with a total of 585 students, then 238 of them were taken randomly as the sample. The technique for collecting data was using three questionnaires, such as students’ religiosity, family’s religious culture, and the discipline in attending TPA at school questionnaire. The research instrument was tested to 120 students. The validity test of the instrument used was the content validity with expert judgement technique, whereas the difference power index tested by product moment correlation formula. Instruments’ reliability was using Cronbach’s Alpha formula. The analysis of prerequisite test that had been used are the normality, linearity, and multi-collinearity test. Data analysis that used was multiple regression. The result shows that: 1) family’s religious culture partially gives significant effect on first grade students’ religiosity; 2) the discipline in attending TPA at school partially doesn’t give significant effect on first grade students’ religiosity; and 3) family’s religious culture and the discipline in attending TPA at school simultaneously give significant effect on first grade students’ religiosity with the effect is 5.2%.